The Moorlands of England and Wales - Simmons, Ian G. (Edinburgh University Press, 2003)
This is a history of the moorlands and the part they have played in English and Welsh history over ten millennia. Ian Simmons combines the perspectives of natural science, archaeology, social history and historical geography, and draws on forty years of exploring and studying the moorlands.